A CRITICAL REVIEW OF SEGMENTATION - Basu, Nilanjan (2014)
Segmentation as a marketing concept has been viewed as the first step in analysing a market so as to divide the market into component parts consisting of a homogeneous group. Segmentation has evolved from being a simple concept to becoming a major guidance for firms’ strategy and resource allocation. This paper critically reviews the segmentation approaches in a business-to-business context taking into account the differentiated need in a specialized B2B market. The methodology adopted is to review and contrast segmentation literature in traditional and contemporary themes. The review details a critical discussion on business-to-business segmentation with a balanced perspective of a marketing theorist and a strategy practitioner.